Pemberian taburia (sprinkle) berpengaruh terhadap lama dan frekuensi diare akut anak - Sopiyandi Sopiyandi; Muhammad Juffrie; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Major causes of mortality in children are diarrhea and pneumonia (25.2% and 15.5%). “Five steps of diarrhea management” is an integrated approach in the management of diarrhea comprising the supplementation of oral rehydration, zinc within 10 days subsequently, breastfeeding and food, selective antibiotics and advice for the mother/family. Zinc supplementation combined with vitamin A and micronutrient on children with the diarrhea had been researchead that result can minimize morbidity, duration and frequency of diarrhea, and the incidence of recurrent diarrhea.Objective: To find out the effect of taburia supplementation (sprinkle) on duration and frequency of diarrhea.Method: The study was randomized controlled trial (RCT) with parallel design. Subject consisted of two groups, the first got therapy of taburia (sprinkle) 1 sachet/day and the second was the control group. Each group got standard diarrhea medication at the health center. Samples consisted of 30 children of 1-5 years old per group and they were obtained by using simple randomization technique. Statistical analysis was performed by using Chi-Square and t-test.Results: Duration of diarrhea of the experiment group was 33.25 ± 18.08 hours (95% CI: 26.49 - 40.00) and the control group was 43.7 ± 19.25 hours (95% CI: 36,50 - 50,89). Frequency of diarrhea of the experiment group was 4.93 ± 3.41 times/day (95% CI: 3,41-3,65) and the control group was 6.33 ± 3.20 times/day (95% CI: 5.13-7.53). The result of statistic test showed that there was effect of taburia supplementation to duration and frequency of diarrhea (p<0.05).Conclusion: Supplementation of taburia (sprinkle) in the standard therapy of diarrhea shortened the duration and minimized the frequency of diarrhea.